International variation in outcomes among people with cardiovascular disease or cardiovascular risk factors and impaired glucose tolerance: Insights from the NAVIGATOR Trial. - Dos Santos, M; Sharma, A; Sun, J; Pieper, K; McMurray, J; Holman, R; Lopes, R (American Heart Association, 2017)
Background Regional differences in risk of diabetes mellitus and cardiovascular outcomes in people with impaired glucose tolerance are poorly characterized. Our objective was to evaluate regional variation in risk of new-onset diabetes mellitus, cardiovascular outcomes, and treatment effects in participants from the NAVIGATOR (Nateglinide and Valsartan in Impaired Glucose Tolerance Outcomes Research) trial. Methods and Results NAVIGATOR randomized people with impaired glucose tolerance and cardiovascular risk factors or with established cardiovascular disease to valsartan (or placebo) and to nateglinide (or placebo) with a median 5-year follow-up. Data from the 9306 participants were categorized by 5 regions: Asia (n=552); Europe (n=4909); Latin America (n=1406); North America (n=2146); and Australia, New Zealand, and South Africa (n=293). Analyzed outcomes included new-onset diabetes mellitus; cardiovascular death; a composite cardiovascular outcome of cardiovascular death, nonfatal myocardial infarction, or nonfatal stroke; and treatment effects of valsartan and nateglinide. Respective unadjusted 5-year risks for new-onset diabetes mellitus, cardiovascular death, and the composite cardiovascular outcome were 33%, 0.4%, and 4% for Asia; 34%, 2%, and 6% for Europe; 37%, 4%, and 8% for Latin America; 38%, 2%, and 6% for North America; and 32%, 4%, and 8% for Australia, New Zealand, and South Africa. After adjustment, compared with North America, European participants had a lower risk of new-onset diabetes mellitus (hazard ratio 0.86, 95% CI 0.78–0.94; P=0.001), whereas Latin American participants had a higher risk of cardiovascular death (hazard ratio 2.68, 95% CI 1.82–3.96; P<0.0001) and the composite cardiovascular outcome (hazard ratio 1.48, 95% CI 1.15–1.92; P=0.003). No differential interactions between treatment and geographic location were identified. Conclusions Major regional differences regarding the risk of new-onset diabetes mellitus and cardiovascular outcomes in NAVIGATOR participants were identified. These differences should be taken into account when planning global trials.